The Concept of Islamic Education in the Perspective of Imam Al Ghazali and Its Relevance in the Contemporary Era - Nurul Indana; Ali Mustofa (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
The purpose of this research in general is to find out the concept of Islamic education from the perspective of Imam Al-Ghazali and its relevance to contemporary Islamic education (today). Islamic education today is faced with various developments and challenges that certainly need to make changes and improvements to be able to make adjustments to these changes. The research that the author uses in terms of sources is library research which aims to reveal educational thoughts, especially regarding the concept of Islamic education from the perspective of Imam Al-Ghazali by using a content analysis approach. The results of this study indicate that the concept of Islamic education from the perspective of Imam Al-Ghazali is relevant to contemporary education (today). This can be seen in terms of educational goals, the concept of educators and students, learning methods, and learning curriculum which in its application prioritizes aspects of intellectual, moral, and spiritual development and educational evaluation. With this, educational institutions are expected to be able to adopt Al-Ghazali's concept of education to develop the potential of students to become human beings who believe and fear God Almighty, have a noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens